2015
DOI: 10.1007/s15010-015-0802-x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity not associated with severity among hospitalized adults with seasonal influenza virus infection

Abstract: We examined seasonal influenza severity [artificial ventilation, intensive care unit (ICU) admission, and radiographic-confirmed pneumonia] by weight category among adults hospitalized with laboratory-confirmed influenza. Using multivariate logistic regression models, we found no association between obesity or severe obesity and artificial ventilation or ICU admission; however, overweight and obese patients had decreased risk of pneumonia. Underweight was associated with pneumonia (adjusted odds ratio 1.31; 95… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 10 publications
3
36
0
1
Order By: Relevance
“…This observation might be consistent with reports of increased inflammation in models of obesity and influenza and severity of ILI in obese persons. (25)(26)(27)(28)(29)(30) Alternatively, increasing BMI is associated with increased frequency of small airways closure and the resulting increased aerosol generation during airway opening as described above may explain the stronger association of BMI with fine than coarse aerosols and lack of association with NP swabs. (31) Our analysis found a clear separation of factors associated with shedding from the nose and those with shedding into aerosols, especially fine particle aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…This observation might be consistent with reports of increased inflammation in models of obesity and influenza and severity of ILI in obese persons. (25)(26)(27)(28)(29)(30) Alternatively, increasing BMI is associated with increased frequency of small airways closure and the resulting increased aerosol generation during airway opening as described above may explain the stronger association of BMI with fine than coarse aerosols and lack of association with NP swabs. (31) Our analysis found a clear separation of factors associated with shedding from the nose and those with shedding into aerosols, especially fine particle aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…This study investigated the burden of pediatric obesity on lower respiratory tract infections using a nationally representative database in the US. Referring to the previous studies which suggested the potential associations between obesity and morbidity including acute respiratory distress and bacteremia, we hypothesized that children with obesity who were hospitalized due to lower respiratory tract infections were more likely to require nonā€invasive or invasive mechanical ventilation, develop bacteremia or septicemia, and needs greater healthcare costs and longer length of hospital stay, compared with children without obesity.…”
Section: Introductionmentioning
confidence: 99%
“…About 190,000 permanent migrants (skilled and family visa categories) and 14,000 humanitarian entrants enter Australia each year 2 . In the majority of migrant source countries, the national immunisation programs include fewer vaccines than are listed on the Australian Standard Vaccination Schedule, and coverage is variable 3 . Refugees invariably arrive from countries with disruptions to health infrastructure, including immunisation programs.…”
Section: Key Recommendations For Addressing the Gap In Immunisationmentioning
confidence: 99%
“…2 In the majority of migrant source countries, the national immunisation programs include fewer vaccines than are listed on the Australian Standard Vaccination Schedule, and coverage is variable. 3 Refugees invariably arrive from countries with disruptions to health infrastructure, including immunisation programs. Primary care and specialist practitioners who see recently arrived migrants and refugees reported a need for catch-up immunisation in these groups.…”
mentioning
confidence: 99%